1999
DOI: 10.7589/0090-3558-35.2.371
|View full text |Cite
|
Sign up to set email alerts
|

Helminths of White-bellied Opossum from Brazil

Abstract: Helminths were collected from 22 specimens of the white-bellied opossum (Didelphis albiventris) captured in the region of Pampulha (Belo Horizonte, Brazil), from May 1985 to March 1995. Ten species of helminths were collected; these included Rhopalias coronatus, Brachylaema migrans, Aspidodera raillieti, Cruzia tentaculata, Turgida turgida, Gongylonema sp., Viannaia hamata, Travassostrongylus orloffi, Trichuris didelphis and Capillaria sp.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0
3

Year Published

2009
2009
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 3 publications
1
15
0
3
Order By: Relevance
“…In Brazil, documented hosts of Capillaria spp. include synanthropic rats (Chieffi et al , 1981; Galvão, 1981), opossum (Quintão e Silva & Costa, 1999), capybaras (Costa & Catto, 1994) and wild canids (Ruas et al , 2008). To the best of our knowledge, there is currently no record of C. hepaticum infections among the paca in Brazil.…”
Section: Introductionmentioning
confidence: 99%
“…In Brazil, documented hosts of Capillaria spp. include synanthropic rats (Chieffi et al , 1981; Galvão, 1981), opossum (Quintão e Silva & Costa, 1999), capybaras (Costa & Catto, 1994) and wild canids (Ruas et al , 2008). To the best of our knowledge, there is currently no record of C. hepaticum infections among the paca in Brazil.…”
Section: Introductionmentioning
confidence: 99%
“…Other studies have also reported that A. raillieti and C. tentaculata are dominant species in other marsupial hosts. Quintão e Silva & Costa (1999), in the state of Minas Gerais, Brazil, and Antunes (2005) in the state of Rio Grande do Sul, Brazil, found high prevalence and high mean intensity rates for C. tentaculata and A. raillieti in D. albiventris. Jiménez et al (2011) found A. raillieti to be a dominant species in component communities in P. opossum and D. marsupialis in French Guiana.…”
Section: Discussionmentioning
confidence: 96%
“…Most of the studies have consisted of reports on helminth species records (Gomes et al, 2003;Thatcher, 2006;Cardia et al, 2016) and taxonomic descriptions (Torres et al, 2007;Adnet et al, 2009;Araújo, 2011;Chagas-Moutinho et al, 2007;Chero et al, 2017). In addition, only a few studies have been conducted on the helminth community structure of Neotropical marsupials (Quintão e Silva & Costa, 1999;Antunes, 2005;Jiménez et al, 2011;Zabott et al, 2017;Costa-Neto et al, 2019;Ramírez-Cañas et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have reported the occurrence of helminth species in D . albiventris (Quintão e Silva & Costa, 1999; Müller, 2005; Pinto et al ., 2014; Ramos et al ., 2016; Zabott et al ., 2017). However, there is a lack of information concerning the structure of helminth communities of this mammal host species, especially under changing environments.…”
Section: Introductionmentioning
confidence: 99%